2022
DOI: 10.1101/2022.04.13.488175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dimensionality of genomic information and its impact on GWA and variant selection: a simulation study

Abstract: Background: Identifying true-positive variants in genome-wide associations (GWA) depends on several factors, including the number of genotyped individuals. The limited dimensionality of the genomic information may give insights into the optimal number of individuals to use in GWA. This study investigated different discovery set sizes in GWA based on the number of largest eigenvalues explaining a certain proportion of variance in the genomic relationship matrix (G). An additional investigation included the chan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…ChipPlusSign also showed greater robustness than Top40k when the genomic prediction was performed using BayesR [8]. Several studies have been conducted to investigate genomic prediction by adding selected variants to regular chip data through either real or simulated datasets [2, 3, 16, 36]. In US Holstein, VanRaden et al [3] investigated the reliability of GEBV for 33 traits when preselected SNP (N = 16k) from WGS were added to a 60k SNP chip.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ChipPlusSign also showed greater robustness than Top40k when the genomic prediction was performed using BayesR [8]. Several studies have been conducted to investigate genomic prediction by adding selected variants to regular chip data through either real or simulated datasets [2, 3, 16, 36]. In US Holstein, VanRaden et al [3] investigated the reliability of GEBV for 33 traits when preselected SNP (N = 16k) from WGS were added to a 60k SNP chip.…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with the ones from Fragomeni et al [2], especially with ChipPlusSign. In a simulated study, Jang et al [16] investigated the dimensionality of genomic information for variant selection and genomic prediction with sequence data. Their results showed that populations with small Ne obtained a maximum accuracy gain of 0.86% to 1.98% when either significant variants or hundreds of variants with high effect sizes preselected from GWAS were added to a 50k SNP chip.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations